2019
DOI: 10.1108/inmr-05-2019-0063
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of customer loyalty in the Indonesian ride-sharing services: offline vs online

Abstract: Purpose This study aims to analyze the effect of service quality on trust, satisfaction and loyalty by adopting two models, namely, conventional service quality model from Parasuraman and information systems (IS) success model from Delone and McLean. Design/methodology/approach Respondents of this study were users of shared-motorcycle services who filled out a complete questionnaire totaling 507. This research used a second-order structural equation model. All question items had quite high reliability and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
4
19
1
3
Order By: Relevance
“…The validity test uses convergent and discriminant concept. Convergent validity looks at the results of Average Variance Extracted (AVE) where the standard must be ≥ 0.50 (Kock, 2018). All the results on the variables in table 3 show the results ≥ 0.50 so it can be said that all variables in this study are valid and meet the measurement standards.…”
Section: Profile Of Respondentsmentioning
confidence: 82%
See 2 more Smart Citations
“…The validity test uses convergent and discriminant concept. Convergent validity looks at the results of Average Variance Extracted (AVE) where the standard must be ≥ 0.50 (Kock, 2018). All the results on the variables in table 3 show the results ≥ 0.50 so it can be said that all variables in this study are valid and meet the measurement standards.…”
Section: Profile Of Respondentsmentioning
confidence: 82%
“…As explained above, the ease of use of an application can determine the user's attitude to like or dislike the application used. Kuswanto, Sundari, Harmadi, & Hariyanti (2020) explains that in the context of online services on application-based transportation, usage is closely related to the quality of the existing system in the application itself which directly impacts user satisfaction and loyalty indirectly. In the long term it will determine whether the user will continue to use the existing mode of transportation application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies (eg, Dionysiou & Tsoukas, 2013; Gajewska et al, 2019; Raza et al, 2020) have investigated the significance of transaction processes in e‐commerce platform usage and customer satisfaction. Having a transaction devoid of internet failures ensures easy platform usage (Kuswanto, Sundari, Harmadi, & Hariyanti, 2020). Using the principal component factor analysis Kuswanto et al (2020) found that website quality, system quality, system assurance and system reliability were critical to the efficiency in e‐commerce platform usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Salah satu transportasi online yang saat ini populer digunakan masyarakat adalah transportasi berbasis aplikasi yang disebut dengan Gojek. Salah satu keunggulan yang dimiliki Gojek adalah tersedianya fitur-fitur dalam aplikasi yang didukung teknologi (Kuswanto et al, 2019). Selain itu, kehadiran Gojek memberikan lapangan pekerjaan bagi sebagian orang yang kehilangan pekerjaan, namun memiliki sepeda motor (Kathan, Matzler and Veider, 2016 (Rahmidani, Kurniawati and Hanifa, 2018).…”
Section: A Pendahuluanunclassified